Intramural Injection with Botulinum Toxin Type A in Piglet Esophagus. The Influencer on Maximum Load and Elongation: A Dose Response Study - Ellebæk, Mark Bremholm; Qvist, Niels; Schrøder, Henrik Daa; Rasmussen, Lars (European Journal of Pediatric Surgery, 2016)
Introduction The treatment of esophageal atresia (OA) is challenging. The main goal is to achieve primary anastomosis. We have previously demonstrated in a pig model that intramural injection of botulinum toxin type A (BTX-A) resulted in significant elongation of the esophagus during tensioning until bursting point. The objectives of the present study were to investigate the influence of different amounts of intramural BTX-A on the stretch–tension characteristics and histological changes of the esophagus in piglets.Materials and Methods A total of 52 piglets were randomized to four groups receiving 2, 4, or 8 units/kg of BTX-A or isotonic saline (placebo). After a 1-hour of rest the esophagus was harvested and subjected to a stretch–tension test and histological examination to assess changes in the density of presynaptic vesicles in the nerve cells.Results Overall, 9 of the 52 animals were excluded from analysis due to problems with the stretch–tension test or death from anesthesia. The maximum loads were higher in the BTX-A groups (2 units/kg: +2.1 N; 4 units/kg: +1.3 N; 8 units/kg: +1.9 N) than the placebo (p = 0.046). There were no significant differences in percentage elongation, or histology.Conclusions This study demonstrated that injection of 2 units/kg BTX-A into a nonanastomosed esophageal wall resulted in a modest increase in the maximum load achieved before bursting; this may be due to the muscle-relaxant effect of BTX-A. BTX-A injection produced no significant effects on elongation or esophageal histology. The clinical usefulness of BTX-A in treatment of OA is still unclear.
Keywords: botulinum toxin type A; esophageal atresia; synaptophysin